Clinical Characteristics, Treatment, and Prognostic Factors of Patients With Primary Extramammary Paget's Disease (EMPD): A Retrospective Analysis of 44 Patients From a Single Center and an Analysis of Data From the Surveillance, Epidemiology, and End Results (SEER) Database - Weng, Shanshan; Zhu, Ning; Li, Dan; Chen, Yurong; Tan, Yinuo; Chen, Jiaqi; Yuan, Ying (Frontiers in Oncology, 2020)
Objective: Primary extramammary Paget’s disease (EMPD) is a rare cutaneous malignancy. The aim of this article is to analyse clinical characteristics, evidence of the prognosis and share treatment experience of primary EMPD. Methods: We extracted 771 patients’ data from the SEER program between 1973 and 2013 to investigate the characteristics and prognosis of patients with EMPD. In addition, 44 patients with primary EMPD in our hospital were retrospectively reviewed for 10 years. Results: Compared with patients younger than 65 years, patients diagnosed at 65-74 years (HR, 2.453) and 75 years or older (HR, 5.750) had shorter survival. Patients with a primary site in the truncal skin (HR, 0.367) or scrotum (HR, 0.246) had better survival compared to those with primary site in the perianal area. Compared with localized EMPD, EMPD with distant (HR, 18.821) and regional (HR, 2.180) metastases were associated with a worse prognosis. Patients who received radiotherapy had decreased survival, with an HR of 2.039. Patients with higher N stage, M stage and AJCC stage had a decreased prognosis (p<0.001). Conclusions: Older age at diagnosis, primary site in the perianal area, distant metastasis, radiotherapy and higher N stage, M stage and AJCC stage may result in decreased survival.